Experimental investigation on the dynamics of an Organic Rankine Cycle evaporator with large-mass fins for the purpose of reducing heat input fluctuations - Jiménez-Arreola, Manuel (2023)
Waste heat recovery from energy-intensive processes using Organic Rankine Cycle (ORC) is a promising effective method to reduce large quantities of energy waste and emissions in the planet. However, one of the main technical challenges that remain for its widespread implementation is related to the intermittent and fluctuating nature of the thermal power available from waste heat sources. This paper presents a test rig to study the effect of the geometry of an ORC evaporator to mitigate the adverse effects of thermal power fluctuations of a waste heat source. An experimental campaign is carried out to analyse the dynamic behaviour of the ORC evaporator, which has a custom geometry aimed at increasing its energy storage capacity. The experimental results show that the evaporator is able to dampen fluctuations of the heat source with cycle durations of up to 12 min. It is shown that an evaporator design consisting of a finned tube heat exchanger with large mass of the fins can have a dramatic effect on the thermal inertia of the system. Such a design can help to dampen or reduce some of the variation of the heat source that is transmitted to the ORC system. This, in turn, can allow the ORC system to work in more stable conditions and reduce the need for aggressive control measures or additional heat storage equipment.